Forced Marriage in the Bride-Napping Case in Sumba-East Nusa Tenggara Linked with Positive Law in Indonesia - Panjaitan, Junifer Dame; Safa’at, Rachmad; Endrawati, Lucky; Sulistio, Faizin (Faculty of Law, Universitas Jenderal Soedirman, 2022)
This study was aimed at revealing the customary and legal issues that were applied in the practice of bride-napping in Sumba, East Nusa Tenggara (NTT). The practice of bride-napping does not give women the freedom to choose their life partner and is a violation of the law that could be punished according to article 328 of the Criminal Code (KUHP). This was field research where the researcher conducted direct interviews with the informants and elaborated the data with the related literature. The method used was normative legal research with a literature study approach. The focus of this study was on the ambiguity of the implementation of laws and regulations on the practice of bride-napping. Indonesia has issued Law of the Republic of Indonesia (UU RI) No.1 of 1974 concerning Marriage which regulates the rights and obligations of each person in marriage. Finally, the result of this study was the practice of bride-napping has deviated from its origins resulting in the violations of human rights.Keywords: forced marriage; bride-napping; Marriage Law